An agriculture- and trade-focused social accounting matrix for Tunisia, 2012 - Thabet, Chokri (International Food Policy Research Institute, 2016)
The purpose of this paper is to document the different steps followed to construct the Tunisian Social Accounting Matrix (SAM) for the year 2012. More precisely, it describes the estimation methods and the nature of data used in the development of the SAM, which has a specific focus on the agriculture and food sectors. The SAM also features a regional disaggregation by three agro-ecological zones. The data used in the construction process are based on two main publications of the “Institut National de la Statistique” (INS): the input-output table (I/O) (2012) and the supply-use table (2012). The I/O (2012) disaggregates the Tunisian economy into 24 sectors, including two agri-food sectors: (1) Agriculture and Fishery, and (2) Food Industries. The supply-use table accounts for about 400 commodities, of which 59 are agriculture, forestry, and fishery products and 64 are processed-food products. Other major information sources used include the household survey publication (2010), the annual report of the Central Bank (2013), the “Annuaire des Statistiques Agricoles” (Ministry of Agriculture 2013c), and the “Budget Economique” (2013).